Offensive game-related indicators that differentiate winning and losing teams and their contribution to scoring a run in Olympic Softball - Athanasakis, P.; Panoutsakopoulos, V.; Sfingos, N.; Kollias, I. A. (Journal of Physical Education and Sport, 2021)
Softball was played in the 2020 Olympic Games, after being excluded for two Olympiads, but with almost half of the games played in each Olympiad from 1996 to 2008. Thus, it is of interest to investigate the game-related indicators that differentiate winning and losing teams as well as their contribution to scoring a run, in an attempt to comprehend contemporary Olympic Softball using data from a past Olympic Tournament in which a much larger number of games was played. The purpose of the study was to examine the offensive game-related parameters that distinguish winning and losing teams in Olympic Softball tournaments and to identify the impact of offensive tactical situations where a run is more likely to be scored. Based on a notational analysis scheme, 2,946 game instants were processed using the Sportscout STA v.3.2 software. Crosstabulation analysis with the chi-square tests established that winning teams had significantly (p < .05) more fly ball batting occasions, had less batted balls in the catcher`s area and more batted balls directed in the center outfield, as well as larger counts of players on bases, stolen bases and runs batted-in. A decision tree analysis using Chi-squared automatic interaction detection (CHAID) revealed that loading the bases with base-runners, batting the ball in the outfield, stealing a base when advancing the base-runners around the bases and using fly ball batting technique were essential to score a run in Olympic Softball. In conclusion, optimum batting action, fast sprinting, enhanced tactical decision making in batting, base-running and base-stealing contribute to the efficiency of the offensive game-related parameters that contribute to achieve a win at an Olympic Softball game.